Evaluating the diagnostic accuracy of ultrasonography in differential diagnosis of adnexal tumours - Smoleń, Agata; Stachowicz, Norbert; Czekierdowski, Artur (Family Medicine & Primary Care Review, 2016)
Background. Ultrasound is a crucial diagnostic procedure in the structural assessment of lesser pelvis organs. It is useful in preliminary diagnosis pertaining to a tumour’s potential malignancy, and visual staging of lesser pelvis neoplasms. Objectives . Evaluation of the diagnostic benefits of grey-scale ultrasonography, colour and spectral Doppler, and three-dimensional ultrasonography in differential diagnosis of adnexal tumours. Material and methods. From a total of 637 patients diagnosed with an ovarian tumour, 202 (31.7%) women presented with malignant tumours and 435 (68.3%) with benign. The patients were classified into the following categories according to FIGO: 52 patients in stage I, 15 in stage II, and the rest in stage III (127 patients) or stage IV (8 patients). Results. The uppermost test accuracy for the superior discriminating threshold value was reported in the case of the semiquantitative analysis of the “Colour’’ score – 81%, and the presence of central vascularity. Other factors included: age, bilateral tumour location with 75% specificity, menopausal status, and presence of papillary projections – 74%. For VFI and VI indices set values amounted to 74% and 73%, respectively. Blood flow assessments measured with PI and RI parameters during spectral Doppler imaging do not appear to present clinically significant diagnostic value. Conclusions . The following parameters have to be considered in initial differentiating diagnostics of adnexal tumours: a) semiquantitative analysis of the “Colour” characteristic and vascular localization in 2D Doppler ultrasound, b) morphological assessment of the tumour in 2D colour Doppler ultrasound, d) evaluation of vascular flow in 3D ultrasound with the implementation of sonoangiography, vascularization index VI, and vascularization-flow index VFI.